Postexercise glucose, insulin, and C-peptide responses to carbohydrate Supplementation: running vs. resistance exercise - Schell, T. C.; Wright, G.; Martino, P.; Ryder, J.; Craig, B. W. (The Journal of Strength and Conditioning Research, 1999)
This study was designed to compare the glucose, insulin, and C-peptide response of 8 men (mean age, 24 ± 1 year) following 40 minutes of nonactivity (NA), a treadmill run (TR) at 75% o2max or resistance exercise (RE) (3 sets × 10 repetitions at 6 stations) at 75% of the one repetition maximum. The subjects were catheterized in an antecubital vein before each trial, and 3-ml serum samples were taken before and 2 hours after treatment. The subjects received a 75-g glucose load 45 minutes after treatment. Significance was set at p < 0.05 for all measurements. The preexercise to immediate postexercise insulin values for the TR trial were significantly reduced, going from 34.6 ± 3.8-19.1 ± 3.0 pmol/L, whereas the RE values were unchanged. The C-peptide responses were reversed, with no change in the TR values and a significant increase in C-peptide after the RE trial; the values went from 0.32 ± 0.06 before to 0.48 ± 0.06 nmol/L after exercise. The 45-minute postexercise glucose load produced similar glucose responses regardless of treatment and significantly elevated RE insulin over the other 2 treatments. An area under the curve showed the total insulin for the RE, TR, and NA trials to be 312.5 ± 58.9, 182.3 ± 19.13, and 161.5± 25.2 pmol/L·min × 102, respectively. The C-peptide response of the RE trial was also significantly higher than NA but not the TR response. In conclusion, the data presented herein suggest that a single bout of RE can promote a greater increase in insulin than running if glucose is present.